(untitled) (Journal of the College of Basic Education, 2022)
The educational process is a communicative activity aimed at stimulating the learner’s motivation and facilitating the learner. It includes a set of activities and decisions taken by the (teacher / teacher) in the educational situation by paying attention to teaching methods and techniques and organizing the forms of the educational situation that the learners interact with in order to achieve the goals envisaged in this process. This is done through intentional design or engineering of the educational environment (organization of educational experiences) in a way that leads to achieving learning for learners and under the supervision of (the teacher / teacher).